Implementation of K.H Ahmad Dahlan's Characteristic Values in History Learning at MA Muhammadiyah Pekanbaru City: Implementasi Nilai-Nilai Ketokohan K.H Ahmad Dahlan dalam Pembelajaran Sejarah di MA Muhammadiyah Kota Pekanbaru - Fera Andini; Isjoni; Asyrul Fikri (Santhet: (Jurnal Sejarah, Pendidikan Dan Humaniora), 2024)
The purpose of this research is to find out the views of students at MA Muhammadiyah Pekanbaru City regarding the figure K.H Ahmad Dahlan, to find out how to implement K.H Ahmad Dahlan's character values ​​in history learning at MA Muhammadiyah Pekanbaru City, and to find out the obstacles to implementing K.H's character values Ahmad Dahlan in history learning. The method in this research is descriptive qualitative type. The results of this research show that students' views on the character and also the values ​​of K.H Ahmad Dahlan have a good view, namely having a religious and nationalistic nature. This shows that MA Muhammadiyah Pekanbaru students also know the values ​​of the figure K.H Ahmad Dahlan and apply them in everyday life. And there are 5 character values ​​of K.H Ahmad Dahlan as stated in Strengthening Character Education (PPK), namely religious values, nationalism, independence, mutual cooperation and integrity. The instilling of K.H Ahmad Dahlan's character values ​​has been carried out well in history learning at the MA Muhammadiyah school in Pekanbaru City. At the MA Muhammadiyah school in Pekanbaru City, apart from studying history, there are Muhammadiyah subjects which also play an important role in implementing the values ​​of the figure of K.H Ahmad Dahlan to students. And there are several obstacles in implementing K.H Ahmad Dahlan's character values ​​in history learning, namely incomplete facilities in the classroom such as the absence of a projector (infocus) in the classroom. This results in the lesson hours being cut so that the time allocated for the learning process becomes less. Apart from that, the obstacle experienced by history teachers at MA Muhammadiyah Pekanbaru is the teacher's lack of pedagogical competence so that teachers have difficulty dealing with the many differences in student character.